2023
DOI: 10.3390/jmse11122344
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Performance and Flow Field Characteristics of Tidal Current Energy Turbine with and without Winglets

Yi Wang,
Bin Guo,
Fengmei Jing
et al.

Abstract: In order to gain a more comprehensive understanding of the influence of winglets on the hydrodynamic performance and flow field characteristics of tidal current energy turbines, two different shapes of winglets are designed, and numerical simulation results for turbines with and without winglets are compared and analyzed. The results show that both shapes of winglets can improve the energy conversion efficiency, and the winglets with a cant angle (60°) are more effective than the flat (0°) winglets; the wingle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The results showed that at the optimum point, a 7% increase in the power generated by the turbine is achieved and that the optimum corresponds to a pitch angle of 33.2 • and a winglet height of 2.04% of the turbine radius. Wang et al [13] evaluated the influence two winglet designs in the performance of a horizontal tidal turbine, obtaining increases of 19% and 26% at the design tip speed ratio of 5. Malla et al [14] performed simulations on a Darrieus-type wind turbine studying the influence of the radius of curvature and the height of an asymmetric winglet on the turbine performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that at the optimum point, a 7% increase in the power generated by the turbine is achieved and that the optimum corresponds to a pitch angle of 33.2 • and a winglet height of 2.04% of the turbine radius. Wang et al [13] evaluated the influence two winglet designs in the performance of a horizontal tidal turbine, obtaining increases of 19% and 26% at the design tip speed ratio of 5. Malla et al [14] performed simulations on a Darrieus-type wind turbine studying the influence of the radius of curvature and the height of an asymmetric winglet on the turbine performance.…”
Section: Introductionmentioning
confidence: 99%